USE OF ICT IN TEACHING AND LEARNING IN SECOND CYCLE INSTITUTIONS: UNDERSTANDING THE TECHNOLOGICAL ASPECT OF THE TPACK MODEL - Asamoah, R.; Asiedu, N. K.; Buadi, D. W. (UDS International Journal of Development, 2022)
This study investigated how ICT can be used to support teaching and learning in public and private second cycle educational institutions in Ghana. The survey approach was used for the study. Using a simple random sampling technique, 182 (112 students and 70 teachers) from the two schools were selected to participate in the study. A comparative study was conducted on the schools’ ICT facilities, how they were being used, the challenges that are encountered and the perception of teachers and students on integration of ICT into teaching and learning in both schools. The findings revealed that both teachers and students have a positive perception about the integration of ICT into teaching and learning. Unstable power supply, system breakdown, unstable internet access and unavailability of ICT integration support staff were identified as the main challenges encountered in using ICT. The study recommended the following: ICT facilities should be provided in all classrooms; the teacher and student laptop project should be expanded to cover every teacher and student, especially in public second cycle institutions and the expansion of internet access points in the various schools. Keywords: TPACK Model, ICT, Teaching with ICT, Learning with ICT, Second cycle Institution